Proximate, vitamins and mineral element analysis of cultivated edible mushrooms: Calocybe indica and Hypsizygus ulmarius - Rajeshbabu, D; Sunilkumar, B; Pandey, Meera; Rao, G Nageswara (Mushroom Research, 2012)
The proximate composition analysis of Hypsizygus ulmarius indicated that it is low in ash (5.135% of dry weight), fat (0.55% of dry weight) and carbohydrate (44.02% of dry weight) but richer in dietary fiber (16.15 % of dry weight) as compared to Calocybe indica. The major sugars present were sugar alcohols. Mannitol content in these mushrooms ranged from 150.15 (C. indica cap) to 242.04 mg/g (H. ulmarius cap) of dry weight of mushroom. Trehalose concentration ranged from 143.18 (H. ulmarius stalk) to 276.3 mg/g (C. indica stalk) and that of arabitol from 8.88 (H. ulmarius cap) to 62.88 mg/g (C. indica stalk). The major fatty acids present in these mushrooms were: oleic (3.5 to 31.4%); linoleic (38.5 to 48.2 %); palmitic (7.0 to 15.6%); and steric (0.38 to 8.8%) acids. Vitamin analysis showed that C. indica contains higher amounts of vitamin B2 and niacin, and lower amounts of vitamins B1 and as compared to H. ulmarius.Â  C. indica was comparatively richer in mineral elements like Na, K, and P than H. ulmarius except for Ca. The results of this study revealed H. ulmarius is nutritionally superior edible mushroom than C. indica.